The Predictive Value of Memory Strategies for Alzheimer's Disease in Subjects with Mild Cognitive Impairment - Ramakers, Inez H.G.B.; Visser, Pieter Jelle; Aalten, Pauline; Maes, Helene L.; Lansdaal, Hendrika G.M.; Meijs, Celeste J.C.; Jolles, Jelle; Verhey, Frans R.J. (Archives of clinical neuropsychology, 2010)
Subjects with Alzheimer's disease (AD) show impaired learning strategies. Whether impaired learning strategies are already present in subjects with prodromal AD remains unknown. The aim of the present study was to investigate the predictive accuracy of learning strategies for AD in subjects with Mild Cognitive Impairment (MCI). Subjects with MCI (n = 202) were selected from the Maastricht Memory Clinic. Subjects were reassessed over a period of 10 years. Fifty-five of the 202 subjects converted to AD. Learning strategies investigated were subjective organization and serial clustering. Lower scores of subjective organization were associated with a higher risk for AD (OR = 2.1, p = .002). Serial clustering did not predict AD. Prodromal AD is characterized by a decreased use of effortful learning strategies. This finding may have implications for the early detection of AD in MCI subjects and for the development of cognitive training programs.